Buckling nanoneedle for characterizing single cells mechanics inside environmental - Ahmad, Mohd. Ridzuan (Institute of Electrical and Electronics Engineers, 2011)
We propose a buckling nanoneedle as a force sensor for stiffness characterization of single cells. The buckling nanoneedle was easily fabricated by using focused ion beam etching from a commercialized atomic force microscope cantilever. There are notable advantages of using buckling nanoneedle for single cells stiffness characterizations. First, severe cell damage from an excessive indentation force could be prevented. Second, large variations in single cells stiffness property could be easily detected either from the dented mark on the cell surface after the indentation and/or by comparing the buckling length of the nanoneedle during the indentation. The calibrations of the buckling nanoneedle were done experimentally and numerically. The calibration results from both methods showed a good agreement. The calibration data show the relationship between the indentation force and the buckling length of the nanoneedle. This relationship was used for obtaining force data during a nanoindentation experiment between a buckling nanoneedle and single cells. We performed in situ measurements of mechanical properties of individual W303 wild-type yeast cells by using a buckling nanoneedle inside an integrated SEM (ESEM)-nanomanipulator system. Finer local stiffness property of single cells was compared at different pressure and different temperature ranges. This detection method of the stiffness variations of the single cells could be applied in the future fast disease diagnosis based on single-cell stiffness analysis.